PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII - Arrafi, Irma Sandi (Departemen Matematika, 2023)
One of the important mathematical abilities to master is mathematical concept understanding. The reality found in the field is that class VII students of SMPN 12 Padang have a relatively low mathematical concept understanding. Applying the Realistic Mathematics Education (RME) method is one way to increase students' mathematical concepts understanding. This research aims to examine how students' mathematical concepts understanding develops while using the RME approach and assess whether students who learn using the RME approach understand mathematical concepts better than students who learn directly in class VIII at SMP Negeri 12 in Padang in the 2022/2023 academic year. This type of research is quasy-experimental and descriptive with the research design Non-equivalent Post-test Only Control Group Design. Class VIII SMP Negeri 12 Padang in the 2022/2023 academic year was the population of this study. The experimental class is class VIII 1 and VIII 2 as control class, then the descriptive subject is VIII.1. The research instrument used was a quiz given at each meeting to see the development of students' mathematical concept understanding in the experimental class and a test of mathematical concept understanding to compare students' mathematical concept understanding in the experimental class and the control class. Keywords – Direct Learning, Mathematical Concept Understanding, Realistic Mathematics Approach